Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1002/chem.200801197
|View full text |Cite
|
Sign up to set email alerts
|

Why Platinum Catalysts Involving Ligands with Large Bite Angle Are so Efficient in the Allylation of Amines: Design of a Highly Active Catalyst and Comprehensive Experimental and DFT Study

Abstract: The platinum-catalyzed allylation of amines with allyl alcohols was studied experimentally and theoretically. The complexes [Pt(eta(3)-allyl)(dppe)]OTf (2) and [Pt(eta(3)-allyl)(DPP-Xantphos)]PF(6) (5) were synthesized and structurally characterized, and their reactivity toward amines was explored. The bicyclic aminopropyl complex [Pt(CH(2)CH(2)CH(2)NHBn-kappa-C,N)(dppe)]OTf (3) was obtained from the reaction of complex 2 with an excess of benzylamine, and this complex was shown to be a deactivated form of cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 60 publications
0
33
0
2
Order By: Relevance
“…[10] This complex is rather unreactive, and so far its use as a catalyst has not been reported. Following previous work on the stabilization of unsaturated, low-valent transition-metal fragments using the widebite-angle, electron-accepting ligand XDPP (bis-2,5-diphenylphosphole xantphos 1), [11,18] in 2009 we isolated the first AuÀH complex featuring a phosphine ligand in the form of the Au 2 H + species, 2-OTf (Scheme 1). [12] The stability of this species is undoubtedly linked to our peculiar ligand, as it is known in the literature that the reaction of [(R 3 P)AuCl] complexes with stoichiometric amounts of hydride sources leads to the formation of Au clusters without observation of Au À H bonds, [13,14] and that an excess of hydride sources can lead to the formation of phosphine-stabilized Au nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…[10] This complex is rather unreactive, and so far its use as a catalyst has not been reported. Following previous work on the stabilization of unsaturated, low-valent transition-metal fragments using the widebite-angle, electron-accepting ligand XDPP (bis-2,5-diphenylphosphole xantphos 1), [11,18] in 2009 we isolated the first AuÀH complex featuring a phosphine ligand in the form of the Au 2 H + species, 2-OTf (Scheme 1). [12] The stability of this species is undoubtedly linked to our peculiar ligand, as it is known in the literature that the reaction of [(R 3 P)AuCl] complexes with stoichiometric amounts of hydride sources leads to the formation of Au clusters without observation of Au À H bonds, [13,14] and that an excess of hydride sources can lead to the formation of phosphine-stabilized Au nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the use of the structurally related POP ligand (β 108 ) 35 and t Bu Xantphos (β 112 ) 36 afforded no product (entries 9 and 11) despite their large bite angle. These ndings clearly indicated that, in addition to a large bite angle, an ef cient chelating ligand should be composed of fully aryl or alkenyl 37 substituted phosphines. Moreover, the very low reactivity when using the Floriani ligand (β 111 ) 38 (entry 10), which is a methylene linked variant of DPEphos, strongly suggests the importance of the linker oxygen in DPEphos and Xantphos.…”
Section: Development and Optimization Of Platinum Catalysismentioning
confidence: 98%
“…The existence of this rapid retro reaction was further supported by crossover experiments. 6 , the addition of benzylamine (8a) led to the formation of a new complex, tentatively assigned as Pt(η 2 H 2 C CHCH 2 NH 2 Bn PF 6 )(dpp xantphos) E. 37 In sharp contrast to their results, our results suggested that (1) complexes D, E, F, and C were in rapid equilibrium, even at room temperature; (2) among them, D was the most stable species even in the presence of excess amounts of nucleophile 3; and (3) the formation of D from C through the elimination of water (C D) was the rate determining step of this catalytic cycle and required a reaction temperature of 50 .…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…Recently, two groups [53,54,56] have reported the use of Pt II phosphine complexes as efficient catalysts for this transformation (Scheme 23).…”
Section: Amination Of Allyl Alcoholsmentioning
confidence: 99%
“…The mechanism has been well-studied, including DFT calculations, [53,54] and it starts with the reduction of Pt II to Pt 0 by b-hydrogen elimination of a coordinated allyl alcohol (Scheme 25, 121). The allyl cation so-generated is attacked by the amine while bound to the Pt II center to give 122.…”
Section: Amination Of Allyl Alcoholsmentioning
confidence: 99%